2013
DOI: 10.3329/jssmc.v5i1.16203
|View full text |Cite
|
Sign up to set email alerts
|

Aetiologies of Vaginal Discharge among Women Presented with Cervical Abnormalities: Experiences at a Tertiary Care Hospital

Abstract: Background: Vaginal discharge is a common gynaecological problem worldwide. It is a common presentation of different gynaecological diseases. Objective: The aim of the study was to find out the aetiological factors responsible for vaginal discharge among the women presented with cervical pathology. Methodology: This cross sectional study was carried out in patients complaining of vaginal discharge attending at Gynaecology department (GOPD) in Dhaka Medical College Hospital (DMCH), Dhaka from March'2006 to Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…21 Brenner showed that 35.1% patients of placenta previa had previous abortion and 11.2% patients of placenta previa had previous cesarean section. 22 In this study, it was observed that 0.8% patients delivered at gestational age 28-31 weeks and 20% patients delivered at >38 weeks. In a study by Sheiner et al it was showed that delivery occurs in gestational age 22-32 weeks 13.4%, 37-41 weeks 51.0%.…”
Section: Discussionmentioning
confidence: 58%
“…21 Brenner showed that 35.1% patients of placenta previa had previous abortion and 11.2% patients of placenta previa had previous cesarean section. 22 In this study, it was observed that 0.8% patients delivered at gestational age 28-31 weeks and 20% patients delivered at >38 weeks. In a study by Sheiner et al it was showed that delivery occurs in gestational age 22-32 weeks 13.4%, 37-41 weeks 51.0%.…”
Section: Discussionmentioning
confidence: 58%